Social Resilience and Livelihood Adaptation of Rice Farming Households in Manyaran, Wonogiri: Shifting from Paddy to Horticulture - Nissa', Zulfa Nur Auliatun; Albab, Azizah Ridha Ulil; Saraswati, Yudhistira; Pratiwi, Liana Fatma Leslie; Damayanti, Elia (Komunitas: International Journal of Indonesian Society and Culture, 2024)
This study investigates the resilience strategies of rice farmers in Manyaran District, Wonogiri Regency, in adapting to agricultural challenges and diversifying into the horticultural sector. The research is grounded in resilience and adaptation in agricultural systems, emphasizing crop diversification as a strategy to sustain farmer livelihoods amidst environmental and economic pressures. In May and June 2024, the study utilized surveys, observations, structured interviews, and a literature review to collect data. 42 rice-farming households across seven villages in Manyaran District were selected through simple random sampling. The sample comprised middle-aged farmers aged 40–50, With an average age of 45 years, as younger populations often migrate to urban areas, leaving agriculture dominated by this demographic. Descriptive data analysis using simple tabulation was employed to illustrate the conditions of the studied area. The findings reveal that farmers in Manyaran District exhibit strong learning capacities, which enhance their resilience. They adapted by transforming rice fields into horticultural areas and experimenting with various horticultural commodities. Technological flexibility, including the use of social media for acquiring and sharing horticultural knowledge, played a crucial role in their adaptation. Information exchange among farmers further contributed to the sustainability of their livelihoods.  This research highlights the importance of crop diversification as a strategy for farmers to adapt to shifting environmental and economic conditions. The results underscore the adaptability and resilience of Manyaran farmers in sustaining agricultural practices despite ongoing challenges, offering insights for broader agricultural adaptation strategies.